Equity research - corsair gaming inc: valuation model - Prydatok, Adam (2021)
This paper is aimed at conducting a valuation of Corsair Gaming, Inc. (CRSR), to understand the potential performance of the stock’s share price for the following 12 months. Two models were used for that end, a discounted cashflows analysis with the Adjusted Present Value framework and a relative valuation using multiples. It is based on subjective assumptions that were fruit of research around the company’s business and its industry. These assumptions are reflected in the forecasted values of key financial captions of the company. Sensitivity and Scenario analysis are performed to better understand the relationship and sensitivity of Corsair’s share price to certain factors. The paper concludes with a target share price and an action recommendation.